Is there a social security tax wedge? - Alessandro Cigno (Institute for the Study of Labor (IZA), 2006)
A Beveridgean pension scheme invariably introduces a wedge between the wage rate and the marginal take-home pay. A Bismarckian one can do so only if it is not actuarially fair, or in the presence of credit rationing. Interestingly, if the two possible sources of distortion are present at the same time, they will tend to offset each other. The distortion may even change sign (the wedge may become a premium). In any case, the same pension contribution will discourage labour less if the scheme is Bismarckian, than if it is Beveridgean.
Keywords: H31; H55; J38; 330; tax wedge; Bismarck; Beveridge; public pensions; implicit pension tax; labour